Peran Micro Teaching dalam Meningkatkan Keterampilan Mengelola Kelas - Aiman, Hallina Hilyatal; Rahmah, Eka Naelia (An-Nuha, 2025)
Students of the Faculty of Tarbiyah face challenges in mastering classroom management skills, which are a crucial part of teachers' pedagogical competence. This study aims to analyze the role of micro teaching in enhancing these skills at the Institute of Qur’anic Sciences (IIQ) Jakarta. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving seven informants. The findings indicate that micro teaching contributes significantly through three stages: knowledge acquisition, skill development, and feedback. Improvements in classroom management skills are evident in students’ abilities to arrange classroom space, maintain order, manage time, build positive relationships, utilize instructional media, and provide effective feedback. It is concluded that micro teaching plays a strategic role in shaping students’ teaching readiness, particularly in the structured and trained development of classroom management skills.